Internationalization - Li, Shanjian (Addison-Wesley, 2007)
"The need for information crosses all borders. Indeed, if you hang out with some Google engineers for a few hours, the odds are good you'll hear someone say 'English is just another language.' Although most developers appreciate the need for internationalization in theory, it's particularly hard to put into practice in Ajax code. Come learn how GWT addresses this challenge head-on by providing libraries and techniques that make I18N-aware applications easy to build, without sacrificing runtime performance."--Resource description page